(3GdgOis - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s ((3HdOI JHQjR s)
(3ChdgG (B:s
(3bO JbOe dfG bHd cJGHfG gPG CQHYI cJH s
(3BNQgG (B:s
(3hEf cfJ de Jage gPG aGbQ cJHfG aSJUd ai bQjH eOI Edi Pdc Ef TGA Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B58 - (3U(B68s
(3GdfSNI HgG MhGTs
(3gPG GdcJGH hGdPi jdjg eJeGKdGfs
(3hdYd CMOgeG (B" (3GdlgOi (B" (3hGdCNQ (B" (3GdgrOi (B"s
(3hQO cPdc ai Qbe (B96 s
(3hgh GdebGdI GdNGeSI ef cJGH GdSHYjf s
(3bQf GdfSN (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs